ANALYSIS OF FINANCIAL STATEMENTS WITH ALTMAN Z-SCORE AND SPRINGATE MODELS ON PT. HERO SUPERMARKET, Tbk - Purba, Arlina Pratiwi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
The company was founded basically in the hope of generating profit, creating market segments or customers and carrying out development in products against the needs of the desired community. In fact, often these assumptions miss and are far from hopeful. Companies that have been doing activities for a certain time sometimes have to be liquidated due to financial difficulties and eventually go into bankruptcy. The threat of bankruptcy does not occur if the company conducts an analysis as early as possible using a company's financial statements. One method of analysis in predicting bankruptcy is the Altman Z-Score method and the Springate method. The purpose of this research is to find out the results of the prediction of potential bankruptcy PT. Hero, Tbk period 2016-2019 using Altman Z-Score and Springate models. Population in this study PT Financial Statements. Hero, Tbk, while the sample in this study is PT Financial Report. PT. Hero, Tbk Period 2016-2019.The results show pt. Hero Supermarket, Tbk based on the Altman Z-Score method, in 2016-2019 the company can be categorized as a company not bankrupt/ healthy company. Based on the Springate method in 2016 and 2019 the company is categorized as a company not bankrupt / healthy, while in 2017 and 2018 is predicted as a bankrupt company/unhealthy company.